PERSEPSI DAN PERAN PENGUNJUNG TERHADAP PENGELOLAAN HUTAN KOTA PATRIOT BINA BANGSA KOTA BEKASI - Sihaloho, Cristina Lestary; Saroinsong, Fabiola Baby; Kalangi, Josephus I. (Sam Ratulangi University, 2022)
This research aims to find out the perception and role of visitors to management in the Patriot Bina Bangsa City Forest (PBBCF) of Bekasi city. The study was conducted from October to November 2021. The selection of respondents was conducted by a simple random sampling method of 97 respondents. The data used is primary data and secondary data. Primary data is collected through questionnaires that have been filled out by visitors who deliberately make visits and visits in 2021. Secondary data was obtained through the Service Technical Execution Unit (STEU) of the PBBCF Bekasi City. Secondary data is also obtained through books obtained from local bookstores and the internet through google scholars in the form of books, journal articles, and thesis related to this research topic, namely the perception and role of visitors to the management of PBBCF Bekasi City. The results of this study showed that the perception of visitors to the management of PBBCF Bekasi City belonged to the category of good (69.62%). This is supported by good activity comfort (73.4%) as well as hard element facilities (66.45%) and soft elements (75.05%) which are good. Visitors already take roles in maintenance roles (81.76%), planning roles (31.6%) as well as roles in development (27.8%).